Enhancing Information Pertaining to Client Characteristics to Facilitate Evidence‐Based Practice. Issue 12 (25th June 2013) - Callahan, Jennifer L.; Heath, Christopher J.; Aubuchon‐Endsley, Nicki L.; Collins, Frank L.; Herbert, Gregory L.
<x xml:space="preserve">Abstract</x> Objective Evidence‐based practice (EBP) includes utilization of empirically supported treatments, application of clinical expertise, and consideration of client characteristics. The following brief report aims to elucidate barriers in the study and dissemination of research regarding these client characteristics. Design Authors examined empirical papers cited on psychologicaltreatments.org (N = 338) and categorized each according to efficacy evidence available pertaining to gender, race/ethnicity, and socioeconomic status (SES). Results Gender was most commonly considered (7% of studies), with less than 2% of studies analyzing efficacy in relation to race/ethnicity or SES. Conclusions Available findings are summarized according to disorder. Researchers are encouraged to attend to client variables in efficacy studies and suggestions are offered for training students to include client variables in EBP.